Propagation of Acupuncture Research Findings: Creating Teams of Clinicians and Scientists to Achieve the Next Level - Crawford, Paul (Med Acupunct, 2020)
Nascent research is beginning to link reduced opioid prescribing and increased well-being with acupuncture. While pain is the most common reason patients see physicians, acupuncture is often recommended to treat it. Due to lack of a common nomenclature around acupuncture treatment protocols, it can be difficult for clinicians to replicate research findings. This article discusses communication of ideas about how the National Institutes of Health (NIH) could help propagate meaningful research findings to practicing acupuncturists. While communication strategies can increase uptake of acupuncture in primary care and pain practices, the NIH could: (1) describe priorities in developing algorithmic acupuncture protocols; (2) require some grant applications to include both clinical and basic science outcomes; (3) develop a “dating service” to match clinical acupuncture researchers and those with the capability and interest to test mechanisms; and (4) initiating fellowships for young investigators that prioritize bringing together the art and science of acupuncture.